PERANCANGAN DAN ANALISIS PENGARUH KEMASAN MADU HUTAN KECAMATAN LUNYUK BESERTA ATRIBUT PENDUKUNGNYA TERHADAP MINAT BELI KONSUMEN - Ayu Desi Septiani; Mega Trishuta Pathiassana; Nila Adelina Saputri; Nurul Gaibi; Lestian Lestian; Nuriman Nuriman; Rimba Trishuta Pathiussina (Universitas Galuh, 2023)
Apis dorsata forest honey is one of the superior products from Lunyuk District, Sumbawa. Not a few Sumbawa people believe that forest honey products from this area have better quality than other areas in Sumbawa Regency. Unfortunately, so far, people in Lunyuk District still manage these products conventionally, including the packaging, which mostly still uses used mineral water bottles or other plastic bottles attached with labels that are easily damaged. This study aims to design forest honey product packaging in Lunyuk District which has a role to increase market opportunities for honey producers in the region. In addition, for consumers, packaging is very useful to get information related to the honey product. The method used in this research is to use a questionnaire that applies a preference scale to 150 respondents consisting of educators and lecturers at the Sumbawa University of Technology. The sampling technique used is simple random sampling. The results showed that the price of honey, the design and size of the forest honey packaging that had been prepared, as well as other supporting attributes of the packaging had a significant effect on buying interest in forest honey in Lunyuk District. In addition, the independent variable (X) can explain 42.5% of the dependent variance (Y) where the remaining 57.5% is influenced by other variables not explained in this study.